Bladder preserving chemoradiotherapy compared to surgery for variants of urothelial carcinoma and other tumors types involving the bladder: An analysis of the National Cancer Database. (January 2021) - Janopaul-Naylor, James Robert; Zhong, Jim; Liu, Yuan; Zhang, Chao; Osunkoya, Adeboye O.; Joshi, Shreyas Subhash; Bilen, Mehmet Asim; Carthon, Bradley; Kucuk, Omer; Hartsell, Lindsey Marie; Shelton, Joseph; Jani, Ashesh B.
Highlights: Muscle invasive bladder cancer with variant histology has worse outcomes. Chemoradiation is associated with similar OS to surgery for variant histology. Adenocarcinoma and SCC have worse OS associated with chemoRT compared to surgery. Abstract: Purpose: For muscle-invasive bladder cancer, bladder preserving chemoradiotherapy (BPCRT) has shown to be a viable alternative for patients with urothelial carcinoma (UCa). Traditionally bladder cancer with variant histology UCa or other tumors types involving the bladder have worse outcomes and BPCRT has been contraindicated. However, there is limited high level evidence for this recommendation. Materials/methods: The National Cancer Database (NCDB) was queried for all patients with Bladder cancer treated from 2004 to 2015 restricted to clinical stage T2-4, N0, M0 who had variants of UCa or other tumors types involving the bladder (e.g. adenocarcinoma and squamous cell carcinoma). Only patients treated with definitive intent with either radical cystectomy or BPCRT after maximal transurethral tumor resection were analyzed. Propensity-score matching was used. Results: 356 patients had BPCRT and 2093 patients had definitive surgery for muscle-invasive bladder cancer limited to variants of UCa and other tumors types involving the bladder. On multivariable analysis worse prognosis was associated with age >65 years old (HR 1.24, p = 0.004) and T4 disease (HR 1.90, p < 0.001). In propensity score weighted sample, there was no statistical significant difference in OS for patients with BPCRT as compared to cystectomy (p = 0.387) and for neuroendocrine, micropapillary or not otherwise specified histology subgroups there was no significant difference. Patients with adenocarcinoma (HR 1.75) or squamous cell carcinoma (HR 1.49) had worse OS associated with BPCRT compared to surgery. Conclusion: From 2004 to 2015, BPCRT in muscle-invasive bladder cancer was associated with similar overall survival compared to cystectomy in patients with selected variant histology but with worse OS for adenocarcinoma or squamous cell carcinoma specifically. As our study has inherent limitations, these hypotheses require validation in a prospective setting and/or with a larger sample size.